O “Novo Ensino Médio” no Pará: uma análise do caderno orientador de projeto de vida da SEDUC - ALMEIDA, Silvano Pereira de (2024)
This article, through bibliographic and documentary research, objective to analyze the “Life Project Notebook” formulated by the Pará State Department of Education (SEDUC/PA) within the scope of the implementation of Law Nº. 13.415/2017, better known as “New High School”. To this, it first provides a brief introduction about the context and content of this reform secondary education law. Then, it outlines some notes about the curricular component “Life Project”. Finally, using Discourse Analysis, based on the theory founded by Michel Pêcheux, it proposes an analysis of the "Life Project Notebook" of the State of Pará.